2017
DOI: 10.3892/or.2017.5502
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-455-3p functions as a tumor suppressor by targeting eIF4E in prostate cancer

Abstract: MicroRNAs (miRNAs) are strongly implicated in various cancers, including prostate cancer. Recently, microRNA-455-3p (miR-455-3p) has been shown to be aberrantly expressed in many tumor tissues, but its functions in tumorigenesis remain unknown. In this study, we investigated the role of miR-455-3p in prostate cancer. We found that miR-455-3p is markedly downregulated in prostate cancer cell lines and clinical tumor specimens. Gain-of-function and loss-of-function studies showed that miR-455-3p promotes prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Thus, our results demonstrate that EPA increased thermogenic markers, in part via regulation of miR-455, a novel EPA target, upstream of PPAR-γ and PPAR-α , which inhibit Ncor to induce key thermogenic biomarkers. However, other studies have also reported potential roles of miR-455 in cancer, specifically as a tumor suppressor [6163]. Taken together these studies suggest potential dual benefits for miR-455 in both cancer and energy balance.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, our results demonstrate that EPA increased thermogenic markers, in part via regulation of miR-455, a novel EPA target, upstream of PPAR-γ and PPAR-α , which inhibit Ncor to induce key thermogenic biomarkers. However, other studies have also reported potential roles of miR-455 in cancer, specifically as a tumor suppressor [6163]. Taken together these studies suggest potential dual benefits for miR-455 in both cancer and energy balance.…”
Section: Discussionmentioning
confidence: 65%
“…MiRNA-455 (miR-455) is recognized as a broadly conserved noncoding RNA that has been implicated in various cancers. The function of miR-455 has been confirmed in prostate cancer [51], gastric cancer [52], and oral squamous cancer cells [53]. However, the potential effect of miR-455-3p has rarely been explored in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…However, miR-455-3p is reportedly downregulated in prostate and colon cancer, and upregulation of miR-455-3p can inhibit the cancer proliferation [43, 44]. These studies imply that miR-455-3p can act as either an oncomiR or a tumor-suppressive miRNA depending on the tumor type.…”
Section: Discussionmentioning
confidence: 99%